The Influence of Citizen Project Learning Model Toward the Students Grade VII Learning Style and Outcome of Gajah Mada Private Junior High School Medan - Setiawan, Deny; Helminsyah, Helminsyah (Jurnal Ilmiah Teunuleh, 2023)
Study this is purposeful For know the influence of the project citizen learning model on results and style Study student . Population study it consists from 7 classes (242 students ) . The class V-1 sample consisted of 39 students for the class experiment and class V-2 totaling 39 students For class control taken _ in a way cluster random sampling . Variable study in dependent learning based m multiple i ntelligences and variables dependent that is results Study and style Study student . Study This is study quasi experiment . Technique data collection with test , documentation , and observation . A data analysis uses statistics inferential . Results _ research test Fh = 0.000, p = 0.05, so the project citizen learning model has an effect in a way simultaneity and significance to results Study student . Test result in sub structure for each variable study is known that interpersonal intelligence has influence which are more big to results Study student that is amounting to 16.24%. Fh test results = 0.00, p = 0.05, the project citizen learning model is influential in a way simultaneity and significance to style Study student . Testing _ in terms of the sub structure of each variable study is known intelligence kinesthetic own more influence _ big to style study students 24.60%. Learning outcomes students in class experiment different with results Study students in class control . Average value of results Study students in class experiment more tall compared to with average value of results Study students in class cont r ol (74.47 ±7.49 >55.64± 7.55 ). Learning style students in class experiment different with style Study students in class control . Average force value Study students in class experiment more tall compared to with mark style Study students in class experiment . (61.54 ± 7.53 > 49.48 ± 7.69 ).